Efficiency of Biochar and Bacillus sp. in The Remediation of Cadmium (Cd) Contaminated Soil - Nur Aini Ahaddiyah; Rossyda Priyadarshini; Bakti Wisnu Widjajani (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Soil contamination occurs when chemical produced by humans pollute and alter the natural conditions of the soil. Contamination caused by heavy metals is very dangerous and can cause harm to the life of organisms through the food chain.  This study aims to determine the effectiveness of biochar and Bacillus sp in reducing Cd heavy metal levels. This study used contaminated soil with Cd levels of 2.59 ppm, pH 7.52, C-organic 1.30%, and CEC 18.35 Cmol/kg. Methodology: The research method used a factorial randomized block design with 2 treatment factors, each consisting of 3 levels: the first factor is biochar dosage, comprising B0 (without biochar), B1 (biochar 20 tons/ha, and B2 (biochar 40 tons/ha) and the second factor is bacterial concentration, comprising C0 (without Bacillus sp), C1 (Bacillus concentration 105), as well as C2 (Bacillus concentration 108). Further analysis if there are different ANOVA results, the BNJ 5% Test will be performed. Findings: the results showed that the combination of biochar 40 tons/ha with bacillus 105 (B2C1) was able to reduce Cd heavy metal levels by 52% over a 4-week incubation period, in addition to reducing heavy metal levels, it also increased soil pH. Cations that are on the surface of the biochar will exchange ions with heavy metals in the soil. Carboxyl –COOH functional groups found in biochar can be released as H+ ions, forming complexes with heavy metal ions and heavy metal ions will be bind to the surface of Bacillus sp. cells containing carboxyl groups, renderingthe the heavy metals unavailable.  Contribution: this study reveals the combination of biochar and Bacillus, where biochar provides an optimal microbial habitat, thuereby increasing remediation efficiency. In addition to knowing the interaction between organic materials with heavy metals and the development of natural and sustainable remediation